Factors Contributing to Brand Loyalty towards Malaysia Higher Educational Institutions - Ramli, Mona Fairuz; ., Salniza Md. Salleh (Journal of Education and Vocational Research, 2015)
This study aimed at filling the gap in the current marketing literature on the driver of brand loyalty towards public higher education institutions in Malaysia. The drivers of brand loyalty studied include university image and perceived teaching and learning quality. Toward meeting the objective, a selfadministrated questionnaire was employed. Smart PLS was used to analyze data from 150 international students of Universiti Utara Malaysia. The result revealed that university image and perceived teaching and learning quality were significantly linked to each other and significantly affected brand loyalty. Proximity this finding will help policy maker to design or develop new marketing strategy in higher education institution which is compatible with student perception as well as to increase the number of international student enrollment.